Effects of source and level of energy or protein supplementation on nitrate toxicity in cattle - Smith, M.W.; Blanding, M.R.; Corah, L.R.; Blasi, Dale A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two experiments were conducted to investigate whether level or source of energy and protein supplementation would reduce the incidence or severity of clinical toxicity in cattle fed forages high in nitrate (NO3). Heavily fertilized sudan hay with 40,000 to 50,000 ppm NO3 was fed in both experiments. The percentage of total blood hemoglobin converted to methemoglobin by nitrate was used to compare treatment effectiveness. Energy supplementation at levels tested in Exp. 1 had no effect on methemoglobin concentration. In Exp. 2, all protein sources (wheat midds, urea, soybean meal) reduced the maximum methemoglobin levels and increased the rate of reconversion to normal hemoglobin.
Keywords: Beef; Nitrate toxicity; Energy; Protein